Increasing insulin resistance predicts adverse pregnancy outcomes in women with gestational diabetes mellitus - Sun, Y-Y; Juan, J; Xu, Q-Q; Su, R-N; Hirst, JE; Yang, H-X (Wiley, 2020)
Background This study aimed to investigate the association between maternal insulin resistance (IR) in the late second trimester and pregnancy outcomes, as well as to identify risk factors of IR among women with gestational diabetes mellitus (GDM).